Digital Human Resource Management and Its Impact on Employee Work Ethic and Performance: A Literature Review - M Leo Febriansyah; Havis Aravik (Penerbit dan Percetakan CV. Picmotiv, 2026)
The development of digital technology has driven changes in human resource management within organizations. Digital human resource management (HRM) functions not only as an administrative system but also as a strategic tool to enhance employee work ethic and performance. This study aims to examine the role of digital HRM in improving work ethic and employee performance using a qualitative descriptive approach through a literature review. Data were collected from relevant scientific journals and academic sources published within the last five years. The findings indicate that digital HRM contributes to improved work efficiency, system transparency, employee motivation, and productivity. However, successful implementation depends on organizational readiness, employees’ digital literacy, and an adaptive organizational culture.